Dietary self-efficacy and social support interactions in junior athletes' acquisition of life skills - Shudo, Yuka; Yamaura, Kazuho; Yasuda, Jun; Sato, Ai; Ebi, Kumiko (Frontiers in Sports and Active Living, 2022)
Objective: This study examined the association between dietary self-efficacy and social support as factors influencing youth life skills acquisition in dietary situations, according to the stages of change. Research Design: This cross-sectional study conducted between April and May 2018 among eight high school baseball teams in Japan. Method: Participants were 180 Japanese high school baseball players. Survey items were life skills (dependent variables), self-efficacy’s influence on dietary control, social support (explanatory variables), and stages of change. Hierarchical multiple regression analysis was used to determine the associations. Results: In the pre-action stage, although there was no significant association between the interaction of self-efficacy and social support and total life skills (β = .11, P = .158), a significant association was observed in the action/maintenance stage (β = .32, P < .05). The interaction between self-efficacy and social support showed a significant association with goal setting in the pre-action stage (β = .19, P < .05) and with communicating in the action/maintenance stage (β = .34, P < .05). Conclusion: The acquisition of life skills in dietary situations can be facilitated by providing social support that considers self-efficacy in relation to dietary control, according to the stages of change.